Comparing the efficacy of different forecasting methods for demand projections in a fast food retail business - Ee, Khong Kie (2008)
In the dissertation, the importance of forecasting in the field of logistics, especially procurement is highlighted. Various forecasting techniques, including na?ve, simple moving average, exponential smoothing, day in week and regression analysis, are discussed and compared. The parameter used to determine the optimal model is the Mean Squared Error (MSE).